Release of prostaglandin D2 by murine mast cells: importance of metabolite formation for antiproliferative activity - C. Haberl; L. Hültner; A. Flügel; M. Falk; S. Geuenich; W. Wilmanns; C. Denzlinger (Mediators of Inflammation)
Prostaglandin (PG) D2 , PGJ2 and Δ12 -PGJ2 are antiproliferative eicosanoids. We investigated the production of PGD2 by murine bone marrow-derived mast cells (BMMC) taking into consideration metabolism of PGD2 to PGD2 and Δ12-PGJ2. PG-metabolites were quantified by high performance liquid chromatography (HPLC) combined with radioimmunoassay (RIA). Stimulated with calcium ionophore A23187 BMMC released eight-fold more PGJ2 and Δ12-PGJ2 than PGD2. Conversion of endogenously produced PGD2 to PGJ2 and Δ12-PGJ2 proceeded rapidly in contrast to metabolism of exogenously added PGD2. The antiproliferative potency of these prostaglandins is demonstrated in vitro. We conclude that determination of PGD2 production by mast cells must take into consideration rapid conversion to active derivatives, which may play a significant role in growth regulation.